On the role of TolC in multidrug efflux: the function and assembly of AcrAB–TolC tolerate significant depletion of intracellular TolC protein. Issue 5 (21st January 2013) - Krishnamoorthy, Ganesh; Tikhonova, Elena B.; Dhamdhere, Girija; Zgurskaya, Helen I.
Summary TolC channel provides a route for the expelled drugs and toxins to cross the outer membrane of Escherichia coli. The puzzling feature of TolC structure is that the periplasmic entrance of the channel is closed by dense packing of 12 α‐helices. Efflux pumps exemplified by AcrAB are proposed to drive the opening of TolC channel. How interactions with AcrAB promote the close‐to‐open transition in TolC remains unclear. In this study, we investigated in vivo the functional and physical interactions of AcrAB with the closed TolC and its conformer opened by mutations in the periplasmic entrance. We found that the two conformers of TolC are readily distinguishable in vivo by characteristic drug susceptibility, thiol modification and proteolytic profiles. However, these profiles of TolC variants respond neither to the in vivo stoichiometry of AcrAB:TolC nor to the presence of vancomycin, which is used often to assess the permeability of TolC channel. We further found that the activity and assembly of AcrAB–TolC tolerates significant changes in amounts of TolC and that only a small fraction of intracellular TolC is likely used to support efflux needs of E. coli. Our findings explain why TolC is not a good target for inhibition of multidrug efflux.